Lean Production in Germany: A Contested Model - Martin Krzywdzinski (The Cambridge International Handbook of Lean Production. Diverging Theories and New Industries around the World, 2021)
The first publications on lean production and the evidence of the competitive advantage Japanese companies held over German competitors (Womack et al. 1990) shocked the German automotive industry of the late 1980s and early 1990s, leading to difficult discussions within companies, trade unions and the academic community about the future development of production systems. While some of the actors pushed for radical change and the adoption of lean production, others pointed out specific conditions in Germany that made directly adopting Japanese models impossible (Turner/Auer 1994; Streeck 1996). The watchword of these latter contributions was “Japan kapieren, nicht kopieren” – understand Japan, but do not copy it.
Keywords: 300